Identifikasi miskonsepsi siswa SMA pada topik ekosistem - Nurhidayah, Latifah; Riandi, Riandi; Solihat, Rini (Assimilation: Indonesian Journal of Biology Education, 2020)
This study aims to obtain information about the misconception of high school students on ecosystem topic. The method that used in this research is descriptive method, and this research takes two schools in Bandung city as sample of the research. Selected schools are schools with high grade passes and low grade passes in Bandung. This study uses three-tier problem as a research instrument combined with CRI method that has been modified. In addition, teacher and student interviews were conducted to obtain information on learning activities that were thought to be factors of misconception. The result of research shows that student has misconception in all concepts that was tested to. In particular, the school with high passing grade has misconception in 12 concept from 27 conception tested.Â  The concept with the highest percentage of students is found in the concept of food webs in context the definition of food web. While the students in schools with low-grade passing experience misconceptions as many as 17 concepts with each context from the 27 concepts tested. The concept that has the highest percentage is concept about energy flow with the context of energy flow sequence. Based on the results of the interviews, it was found that learning was conducted by using lecture method and used the power-point presentation as the only media in learning. With this kind of learning, students with misconceptions are mostly bored with learning, and lose interest in caring for teachers. In addition, most students admitted that the students do not understand the explanation given by the teacher, so look for alternative sources of referral of learning such as textbooks, worksheets, and reference sources from the internet.